2006
DOI: 10.1210/jc.2006-1706
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and Age-Specific Reference Curves for Serum Markers of Bone Turnover in Healthy Children from 2 Months to 18 Years

Abstract: This study provides reference curves for OC, BALP, CTX, ICTP, and TRAP5b in healthy children. Taller and heavier individuals for age had greater bone marker concentrations, likely reflecting greater growth velocity. SDS for markers of bone formation, collagen degradation, and phosphatases were each independently correlated, suggesting they derive from the same biological processes. The possibility of calculating SDS will facilitate monitoring of antiresorptive therapy or disease progression in children with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
169
2
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(196 citation statements)
references
References 47 publications
19
169
2
6
Order By: Relevance
“…Our results showed that the levels of all biochemical bone markers in both patients and controls were highest in the preearly-pubertal years, followed by an overall decrease through puberty and postpubertal years, in accordance with other studies of bone markers in children, adolescents, and adults (12,(15)(16)(17)(18)(19). Previously, bone marker values have been shown to increase during early-mid puberty (Tanner breast developmental stages 2 and 3), corresponding to increasing height velocity (15,17,18).…”
Section: Rett Syndrome and Low Bone Turnoversupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that the levels of all biochemical bone markers in both patients and controls were highest in the preearly-pubertal years, followed by an overall decrease through puberty and postpubertal years, in accordance with other studies of bone markers in children, adolescents, and adults (12,(15)(16)(17)(18)(19). Previously, bone marker values have been shown to increase during early-mid puberty (Tanner breast developmental stages 2 and 3), corresponding to increasing height velocity (15,17,18).…”
Section: Rett Syndrome and Low Bone Turnoversupporting
confidence: 92%
“…Furthermore, biochemical bone markers have not been associated with measures of bone mineral density or low-energy fractures in RTT. Studies on biochemical bone markers in healthy persons have reported high levels in early childhood, peaking in puberty, and decreasing to stable levels in the mid-20s (12,(15)(16)(17)(18)(19), but the level of biochemical bone markers in children and adolescents with RTT is unknown.…”
mentioning
confidence: 99%
“…(8,(22)(23)(24)(25) Although prior studies have demonstrated that biomarkers of bone metabolism were positively correlated with growth velocity, (7,24) these studies were limited to correlations between biomarkers and growth velocity without consideration of the independent effects of pubertal maturation, bone mass, and bone accrual on biomarker levels. Our data in healthy controls demonstrates that Tanner stage, sex, WB-BMC, height velocity, and WB-BMC accrual rates were all significant and independent determinants of bone biomarker levels during childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…(6,7) Biomarkers of bone metabolism in children and adolescents have traditionally been interpreted in the context of sex and age or pubertal stage. (8) However, overall skeletal mass [e.g. whole body bone mineral content (WB-BMC)], height velocity, and rates of bone accrual may also be important determinants.…”
mentioning
confidence: 99%
“…Until now, paediatric reference data have mainly been used for diagnosing poor bone acquisition in children who are suffering from multiple fractures, diseases or receiving medical treatments affecting bone metabolism. 11,14 Bone reference data may be not only a diagnostic tool for children with bone diseases 15 but may also serve to monitor apparently healthy subjects and to identify those who may benefit from specific interventions to improve bone health.…”
Section: Introductionmentioning
confidence: 99%